2013
DOI: 10.1038/ngeo2028
|View full text |Cite
|
Sign up to set email alerts
|

Copper enrichment in arc magmas controlled by overriding plate thickness

Abstract: Porphyry copper systems supply about 75% of the world’s copper1. They form above subduction zones and are preferen- tially associated with calc-alkaline magmas1,2. Such magmas result from continuous iron depletion during differentiation, in contrast to tholeiitic magmas that show initial iron enrichment during differentiation3. The formation of calc-alkaline magmas is favoured by high water content and oxygen fugacity4–7. These characteristics, as well as magmatic metal contents, are thought to be imparted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(150 citation statements)
references
References 25 publications
6
144
0
Order By: Relevance
“…Thus, the thickened modern south Tibetan crust is not a robust indicator of the partial melting of metabasalt in the lower crust during the Miocene. In fact, the crustal thickness in the Andes reaches 68 km (Chiaradia, 2014), however, adakites associated with porphyry Cu deposits are all slab melts (Sun et al, 2010), which are closely related to the subduction of oceanic ridges (Cooke et al, 2005;Sun et al, 2010).…”
Section: Formation Of Gangdese Adakitesmentioning
confidence: 99%
“…Thus, the thickened modern south Tibetan crust is not a robust indicator of the partial melting of metabasalt in the lower crust during the Miocene. In fact, the crustal thickness in the Andes reaches 68 km (Chiaradia, 2014), however, adakites associated with porphyry Cu deposits are all slab melts (Sun et al, 2010), which are closely related to the subduction of oceanic ridges (Cooke et al, 2005;Sun et al, 2010).…”
Section: Formation Of Gangdese Adakitesmentioning
confidence: 99%
“…While sulfide saturation in the lower crust inevitably drives the amount of Cu down during magmatic evolution of calc-alkaline magmatic suites (Chiaradia 2014), the oxidation state of sulfur can dramatically change upon magma ascent and decompression (Matjuschkin et al 2016). Indeed, for a magma having ƒO 2 buffered around NNO + 1 to NNO + 2 such as the ore-forming porphyries at Coroccohuayco, magmatic sulfur is dominantly a reduced species at lower crustal pressures (Matjuschkin et al 2016), but is dominantly in the form of more oxidized sulfates at upper crustal pressures.…”
Section: Resultsmentioning
confidence: 99%
“…11), respectively. Initial melt Cu concentrations were assumed to be 20-50 ppm as commonly advocated for such intermediate arc magmas (Cline and Bodnar 1991;Steinberger et al 2013;Chiaradia 2014). Fluid/melt partition coefficients for S were computed from the calibration of Masotta et al (2016) using the whole-rock composition of the porphyries and ranged from 2 to 15.…”
Section: Melt Fractionmentioning
confidence: 99%
“…Ruscitto et al 2012), the best evidence for slab devolatilization beneath volcanic arcs is based on a combination of experimental studies, high-pressure phase equilibria considerations and mass-balance calculations (e.g. Kerrick & Connolly 1998, 2001aAlt et al 2013;Jego & Dasgupta 2013, 2014. Evidence from these studies converge on the notion that much of the subducted sulphur and carbon is returned to the deeper mantle rather than recycled, thus suggesting only moderate devolatilization at the P-T conditions relevant to subduction environments (e.g.…”
Section: Devolatilization Of the Subducting Slabmentioning
confidence: 95%
“…1). Through a global review of copper porphyries, it has been shown that copper sulphide accumulations are most significant in arcs with thick overriding plates and with magmas exhibiting strong calc-alkaline (iron depletion) trends; this suggests that plate thickness exerts a first-order control on magma differentiation and metal segregation (Chiaradia 2014). At Merapi volcano, Indonesia, metals and sulphur outgas in the same proportions as found in sulphide minerals contained in minerals as inclusions, suggesting that entrainment of sulphide and its subsequent dissolution is the source for outgassing metals (Nadeau et al 2010).…”
Section: The Role Of Volatiles In Subvolcanic Processes and Eruptionmentioning
confidence: 99%